Superconductor superfluid density from the Bardeen–Cooper–Schrieffer/Bose crossover theory - Israel Chávez; Marcela Grether; Manuel de Llano (SN Applied Sciences, 2022)
Article Highlights Superfluid density of a superconductor (SC) is calculated with the BCS-Bose crossover extended with two-hole of Cooper pairs. In the weak-coupling extreme in 3D we found good agreement with conventional SCs with quadratic dispersion relation. For high-T $$_c$$ c SCs (cuprates) in the intermediate coupling in 2D with a linear relation; results compare well with the data.